THE RESULTS OF ONLINE LEARNING ON STUDENTS' LEARNING MOTIVATION AT SMP NEGERI 3 KASIHAN BANTUL YOGYAKARTA - Tenisha Nur Rahmawati; Eko Perianto; Enik Nurkholidah (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to determine the effects of distance learning (online) on the learning motivation of class VII A students of SMP Negeri 3 Kasihan in the academic year 2021/2022. The method used in this study is a correlation technique with a quantitative approach. The subjects in this study were grade VII A students at SMP Negeri 3 Kasihan in the 2021/2022 academic year. Sampling in this study used a purposive sampling technique with a population of 158 students and a sample of 34 students of class VII A at SMP Negeri 3 Kasihan was obtained. Collecting data using a distance learning questionnaire and learning motivation. Based on the data analysis performed, the obtained simple linear regression equation model Y= 44,192 + 0,483 X which means that distance learning has no effect on students' learning motivation. Based on the value of Fcount =2,969 with a significance level greater than 5% (sig. 0.05), which is equal to 0.095, it means that there is no effect of distance learning students' learning motivation.